Metal monatomic catalyst as well as preparation method and application thereof
A method for preparing metal single-atom catalysts on aluminum powder addresses the complexity and agglomeration issues, enabling flexible loading and large-scale synthesis with enhanced thermal performance.
Patent Information
- Application Number
- CN202411469925.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The preparation method of single-atom catalysts is complicated, the loading amount is difficult to control, and agglomeration to form nanoparticles is easy to occur during the synthesis process.
A method involving the impregnation of metal salt precursors onto aluminum powder, followed by rotary evaporation and calcination, to form a metal single-atom catalyst with a loading amount of 0.1% to 5% on the surface of aluminum powder.
The method allows for flexible control of metal loading, simple process, and large-scale synthesis of single-atom catalysts, with improved thermal properties and high dispersion of metal atoms.
Smart Images

Figure CN119158574A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of single-atom catalyst preparation, and in particular relates to a metal single-atom catalyst and a preparation method and application thereof. Background Art
[0002] Single-atom catalysts are a special type of supported metal catalysts, in which all metal components on the support exist in the form of single-atom dispersion, and there are no same-atom metal-metal bonds. Single-atom catalysts exhibit significantly different activity, selectivity and stability from conventional nanocatalysts due to their special structure. Single-atom catalysis has quickly become a research frontier in the field of catalysis, making it possible to elucidate the structure-activity relationship of catalysts at the atomic and molecular scales.
[0003] Single-atom catalysts have higher catalytic activity than nanoparticle catalysts and nanocluster catalysts because they can achieve nearly 100% atomic utilization, thus reducing the amount of loaded metal elements such as lead and copper. Generally speaking, the preparation method of single-atom catalysts is complicated, the laboratory single synthesis yield is about 0.1-10 g, the metal loading is usually less than 1%, and the type of loaded metal has certain limitations. In the preparation process of single-atom catalysts with high metal loading, it is very easy for the loaded metal atoms to agglomerate to form nanoparticles, resulting in the failure of the single-atom catalyst synthesis or affecting the catalytic activity of subsequent reactions.
[0004] Therefore, it is particularly important to develop and design a general preparation method for single-atom catalysts with simple synthesis methods, controllable metal types and loading amounts, and large-scale production. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a metal single atom catalyst and its preparation method and application, so as to solve the technical problems of the prior art that the preparation method of single atom catalyst is complicated, the loading amount is difficult to control, and the agglomeration to form nanoparticles is easy to occur during the synthesis process.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses for the first time a metal single-atom catalyst, which is formed by uniformly loading a metal single-atom material on the surface of aluminum powder.
[0007] Preferably, the loading amount of the metal single atom material is 0.1% to 5% of the mass of the aluminum powder.
[0008] Preferably, the metal single atom material includes one or more of Fe, Co, Mn, Cu and Pb.
[0009] Preferably, the aluminum powder is nano aluminum powder or micro aluminum powder.
[0010] The present invention also discloses a method for preparing the above metal single atom catalyst, comprising the following steps: 1) Using the impregnation method, the metal salt precursor is used as the solute, added to the solvent and ultrasonically mixed, and then the carrier aluminum powder is added and fully stirred at room temperature until the metal salt precursor is adsorbed onto the surface of the aluminum powder; 2) The solvent is completely removed by rotary evaporation to obtain aluminum powder adsorbing the metal salt precursor; 3) The aluminum powder adsorbed with the metal salt precursor is fully ground, and then calcined in a protective gas atmosphere under sealed conditions. After the metal precursor is fully pyrolyzed, a metal single atom catalyst is obtained.
[0011] Preferably, in step 1), the metal in the metal salt precursor is one or more of Fe(II), Co(II), Cu(II) and Pb(II); The mass ratio of the metal in the metal salt precursor to the micron-sized aluminum powder is (0.1-5):100; The ultrasonic treatment time is 10~30 min; the stirring time is 8~24 h.
[0012] Further preferably, the metal salt precursor is selected from one or more of decacarbonyl dimanganese, octacarbonyl dicobalt, dodecacarbonyl triiron, ferric acetylacetonate, cobalt acetylacetonate, copper acetylacetonate and lead acetylacetonate.
[0013] Preferably, in step 2), during the process of removing the solvent by rotary evaporation, the water bath temperature of the rotary evaporator is set to 50-70°C, the rotation speed is set to 120-140 rpm, and the duration is 30-120 min.
[0014] Preferably, in step 3), the temperature regime of the calcination treatment is: starting from room temperature, heating to 100-450°C at a heating rate of 1-5°C / min, and keeping the temperature for 1-3 h.
[0015] The present invention also discloses the effect of the above-mentioned metal single-atom catalyst on improving the thermal properties of the material.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The metal single atom catalyst disclosed in the present invention uses aluminum powder material as a carrier, and uses methods such as rotary evaporation and chemical transfer reaction to evenly disperse metal single atoms on the surface of aluminum powder to form a single atom catalyst.
[0017] Furthermore, the loading amount of the metal single atom can be flexibly controlled by the amount of the metal precursor added, which is generally 0.1 wt.%~5 wt.%. Corresponding to the corresponding metal precursor, the metal single atom may include Fe, Co, Mn, Cu, Pb, etc.
[0018] The preparation method of the metal single-atom catalyst disclosed in the present invention has a simple process, relatively low cost, and the catalyst output and single-atom loading can be flexibly adjusted. According to the different capacities of the quartz tube, different masses (0.1-100 g) of aluminum powder carrier and metal salt precursor mixture can be loaded, and finally large-scale synthesis of aluminum-based single-atom catalysts can be achieved. The method of the present invention is suitable for the loading of various metal single atoms, which effectively solves the shortcomings of the prior art such as complex synthesis, difficult control of single-atom loading and difficulty in large-scale preparation of catalysts, and improves the universality of the single-atom catalyst synthesis method. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 are X-ray diffraction (XRD) diagrams of original micron-sized aluminum powder and metal single-atom catalysts prepared in Examples 1 to 4 of the present invention; Figure 2 is a spherical aberration corrected scanning transmission electron microscope (AC-STEM) image of the Fe single atom catalyst prepared in Example 1; Figure 3 is a spherical aberration corrected scanning transmission electron microscope (AC-STEM) image of the Co single atom catalyst prepared in Example 2; Figure 4 is a spherical aberration corrected scanning transmission electron microscope (AC-STEM) image of the Cu single atom catalyst prepared in Example 3; Figure 5 is a spherical aberration corrected scanning transmission electron microscope (AC-STEM) image of the Pb single atom catalyst prepared in Example 4; Figure 6 is the synchrotron radiation image of the Fe single atom catalyst prepared in Example 1; Figure 7 is the synchrotron radiation image of the Co single atom catalyst prepared in Example 2; Figure 8 is the synchrotron radiation image of the Cu single atom catalyst prepared in Example 3; Fig. 9 is the synchrotron radiation image of the Pb single atom catalyst prepared in Example 4; Fig.10 It is a synchronous thermal analysis (TG-DSC) diagram of the original micron-sized aluminum powder and the metal single-atom catalyst prepared in Examples 1 to 4 of the present invention. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0021] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0022] The present invention is further described in detail below in conjunction with the accompanying drawings: Example 1 This embodiment provides a single-atom catalyst with micron-sized aluminum powder as a carrier and a theoretical Fe loading of 0.2%, which is prepared by the following steps: Weigh 0.00596 g of triiron dodecacarbonyl and place it in a 150 mL eggplant-shaped flask, and add 50 mL of anhydrous ethanol to the flask. After ultrasonic dispersion for 30 min, a uniform solution is obtained. Weigh 1 g of micron-sized aluminum powder and place it in the solution. After ultrasonic dispersion for 30 min, stir at 25 °C for 24 h. The solvent is removed by rotary evaporation to obtain a gray solid. After drying at 60 °C for 10 h, the solid is fully ground. The powder is transferred to a quartz tube and sealed. The sealed quartz tube is placed in a tube furnace and heated to 150 °C at 5 °C / min in a protective gas atmosphere. The temperature is maintained at 150 °C for 1 h. After cooling, the solid is washed and filtered to obtain the gray target product, i.e., the iron single atom catalyst.
[0023] Figure 1 The X-ray diffraction (XRD) patterns of Example 1 of the present invention and micron-sized aluminum powder are schematically shown. Figure 1 As shown, in Figure 1 In the XRD test results of Example 1, there are only diffraction peaks belonging to the micron-sized aluminum powder carrier, and no diffraction peaks related to Fe nanoparticles and their oxides, which indirectly illustrates that the loaded Fe has a very high dispersion. Figure 2This is a spherical aberration corrected scanning transmission electron microscope (AC-STEM) image of Example 1 of the present invention. Figure 2 As shown in Figure 2, AC-STEM proves that Fe exists in the form of single atoms on the surface of the micron-sized aluminum powder carrier. Figure 6 As shown, according to the synchrotron radiation data, no Fe-Fe bond was found in the Fe / Al catalyst, proving that Fe mainly exists in the form of single atoms. The Fe content in the Fe metal single atom catalyst prepared in Example 1 was measured by ICP-AES, and the actual Fe loading was calculated from the ICP-AES results to be 0.19%.
[0024] The thermal performance test of the Fe single atom catalyst prepared in Example 1 and the original micron-sized aluminum powder carrier without single atom loading was carried out. The TG-DSC results are as follows: Fig.10 As shown. Fig.10 As shown in (a), the weight of the unmodified micron-sized aluminum powder increased to 156.3%, the exothermic peak temperature of the reaction was 1072.61 °C, and the heat released was 136.81 mJ / mg. Fig.10 As shown in (b), the weight of the Fe single atom catalyst prepared in Example 1 increased to 168.8%, the exothermic peak temperature of the reaction was advanced to 998.29°C, and the heat released was 170.12 mJ / mg. The heat released by the Fe single atom catalyst prepared in Example 1 was 24.35% higher than that of the unmodified micron-sized aluminum powder.
[0025] Example 2 This embodiment provides a single-atom catalyst with micron-sized aluminum powder as a carrier and a theoretical Co loading of 0.2%, which is prepared by the following steps: Weigh 0.0058 g of dicobalt octacarbonyl and place it in a 150 mL eggplant-shaped flask, and add 50 mL of anhydrous ethanol to the flask. After ultrasonic dispersion for 30 min, a uniform solution is obtained. Weigh 1 g of micron-sized aluminum powder and place it in the solution. After ultrasonic dispersion for 30 min, stir at 25 °C for 24 h. The solvent is removed by rotary evaporation to obtain a gray solid. After drying at 60 °C for 10 h, it is fully ground. The powder is transferred to a quartz tube and sealed. The sealed quartz tube is placed in a tube furnace and heated to 180 °C at 5 °C / min in a protective gas atmosphere. It is maintained at 180 °C for 1 h. After cooling, it is washed and filtered to obtain the gray target product, i.e., the cobalt single atom catalyst.
[0026] Figure 1 The X-ray diffraction (XRD) patterns of Example 2 of the present invention and micron-sized aluminum powder are schematically shown. Figure 1 As shown, in Figure 1In the XRD test results of Example 2, there are only diffraction peaks belonging to the micron-sized aluminum powder carrier, and no diffraction peaks related to Co nanoparticles and their oxides, which indirectly illustrates that the loaded Co has a very high dispersion. Figure 3 This is a spherical aberration corrected scanning transmission electron microscope (AC-STEM) image of Example 2 of the present invention. Figure 3 As shown in Figure 2, AC-STEM proves that Co exists in the form of single atoms on the surface of the micron-sized aluminum powder carrier. Figure 7 As shown, according to the synchrotron radiation data, no Co-Co bond was found in the Co / Al catalyst, proving that Co exists mainly in the form of a single atom. The Co content in the Co metal single atom catalyst prepared in Example 2 was measured by ICP-AES, and the actual Co loading was calculated to be 0.19% from the ICP-AES results.
[0027] The thermal performance test of the Co single atom catalyst prepared in Example 2 was carried out, and the TG-DSC results are as follows: Fig.10 As shown in (c), the weight of the Co single atom catalyst prepared in Example 2 increased to 158%, the exothermic peak temperature of the reaction was advanced to 1031.18°C, and the heat released was 158.03 mJ / mg. The heat released by the Co single atom catalyst prepared in Example 2 was 15.51% higher than that of the unmodified micron-sized aluminum powder.
[0028] Example 3 This embodiment provides a single-atom catalyst with micron-sized aluminum powder as a carrier and a theoretical Cu loading of 0.2%, which is prepared by the following steps: Weigh 0.0082 g of copper acetylacetonate and place it in a 150 mL eggplant-shaped flask, and add 50 mL of anhydrous ethanol to the flask. After ultrasonic dispersion for 30 min, a uniform solution is obtained. Weigh 1 g of micron-sized aluminum powder and place it in the solution. After ultrasonic dispersion for 30 min, stir at 25 ° C for 24 h. The solvent is removed by rotary evaporation to obtain a gray solid. After drying at 60 ° C for 10 h, it is fully ground. The powder is transferred to a quartz tube and sealed. Then the sealed quartz tube is placed in a tube furnace and heated to 150 ° C at 5 ° C / min in a protective gas atmosphere. Maintain at 150 ° C for 1 h, and after cooling, wash and filter to obtain the gray target product, that is, the copper single atom catalyst.
[0029] Figure 1 The X-ray diffraction (XRD) patterns of Example 3 and micron-sized aluminum powder of the present invention are schematically shown. Figure 1 As shown, in Figure 1In the XRD test results of Example 3, there are only diffraction peaks belonging to the micron-sized aluminum powder carrier, and no relevant diffraction peaks of Cu nanoparticles and their oxides are found, which indirectly illustrates that the loaded Cu has a very high dispersion. Figure 4 This is a spherical aberration corrected scanning transmission electron microscope (AC-STEM) image of Example 3 of the present invention. Figure 4 As shown in Figure 2, AC-STEM proves that Cu exists in the form of single atoms on the surface of the micron-sized aluminum powder carrier. Figure 8 As shown, according to the synchrotron radiation data, no Cu-Cu bond was found in the Cu / Al catalyst, proving that Cu mainly exists in the form of a single atom. The Cu content in the Cu metal single atom catalyst prepared in Example 3 was measured by ICP-AES, and the actual Cu loading was calculated to be 0.18% from the ICP-AES results.
[0030] The thermal performance test of the Cu single atom catalyst prepared in Example 3 was carried out, and the TG-DSC results are as follows: Fig.10 As shown in (d), the weight of the Cu single-atom catalyst prepared in Example 3 increased to 163.5%, the exothermic peak temperature of the reaction was advanced to 1049.46°C, and the heat released was 144.38 mJ / mg. The heat released by the Cu single-atom catalyst prepared in Example 3 was 5.53% higher than that of the unmodified micron-sized aluminum powder.
[0031] Example 4 This embodiment provides a single-atom catalyst with micron-sized aluminum powder as a carrier and a theoretical Pb loading of 0.2%, which is prepared by the following steps: Weigh 0.0039 g of lead acetylacetonate into a 150 mL eggplant-shaped flask, and add 50 mL of anhydrous ethanol to the flask. After ultrasonic dispersion for 30 min, a uniform solution is obtained. Weigh 1 g of micron-sized aluminum powder and place it in the solution. After ultrasonic dispersion for 30 min, stir at 25 °C for 12 h. The solvent is removed by rotary evaporation to obtain a gray solid. After drying at 60 °C for 10 h, the solid is fully ground. The powder is transferred to a quartz tube and sealed. The sealed quartz tube is then placed in a tube furnace and heated to 450 °C at 5 °C / min in a protective gas atmosphere. The tube is maintained at 450 °C for 1 h. After cooling, the solid is washed and filtered to obtain the gray target product, i.e., the lead single atom catalyst.
[0032] Figure 1 The X-ray diffraction (XRD) patterns of Example 4 and micron-sized aluminum powder of the present invention are schematically shown. Figure 1 As shown, in Figure 1In the XRD test results of Example 4, there are only diffraction peaks belonging to the micron-sized aluminum powder carrier, and no relevant diffraction peaks of Pb nanoparticles and their oxides are found, which indirectly illustrates that the loaded Pb has a very high dispersion. Figure 5 This is a spherical aberration corrected scanning transmission electron microscope (AC-STEM) image of Example 4 of the present invention. Figure 5 As shown in Figure 2, AC-STEM proves that Pb exists in the form of single atoms on the surface of the micron-sized aluminum powder carrier. Fig. 9 As shown, according to the synchrotron radiation data, no obvious Pb-Pb bond appears in the Pb / Al catalyst, proving that Pb exists mainly in the form of single atoms. The Pb content in the Pb metal single atom catalyst prepared in Example 4 was measured by ICP-AES, and the actual Pb loading was calculated to be 0.21% from the ICP-AES results.
[0033] The thermal performance test of the Pb single atom catalyst prepared in Example 4 was carried out, and the TG-DSC results are as follows: Fig.10 As shown in (e), the weight of the Pb single atom catalyst prepared in Example 4 increased to 160.7%, the exothermic peak temperature of the reaction was advanced to 1006.82 °C, and the heat released was 148.54 mJ / mg. The heat released by the Pb single atom catalyst prepared in Example 4 was 8.57% higher than that of the unmodified micron-sized aluminum powder.
[0034] The single-atom catalysts of different types of metal atoms loaded on the micron-sized aluminum powder carriers synthesized in Examples 1-4 further prove that the preparation method of the present invention has universal applicability, and the obvious changes or modifications derived therefrom are still within the protection scope of the preparation method of the present invention.
[0035] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A metal single atom catalyst, characterized in that: The metal single atom catalyst is formed by uniformly loading the metal single atom material on the surface of aluminum powder.
2. The metal single atom catalyst according to claim 1, characterized in that The loading amount of the metal single atom material is 0.1% to 5% of the mass of the aluminum powder.
3. The metal single atom catalyst according to claim 1, characterized in that The metal single atom material includes one or more of Fe, Co, Mn, Cu and Pb.
4. The metal single atom catalyst according to claim 1, characterized in that The aluminum powder is nano aluminum powder or micron aluminum powder.
5. The method for preparing the metal single atom catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Using the impregnation method, the metal salt precursor is used as the solute, added to the solvent and ultrasonically mixed, and then the carrier aluminum powder is added and fully stirred at room temperature until the metal salt precursor is adsorbed onto the surface of the aluminum powder; 2) The solvent is completely removed by rotary evaporation to obtain aluminum powder adsorbing the metal salt precursor; 3) The aluminum powder adsorbed with the metal salt precursor is fully ground, and then calcined in a protective gas atmosphere under sealed conditions. After the metal precursor is fully pyrolyzed, a metal single atom catalyst is obtained.
6. The method for preparing a metal single atom catalyst according to claim 5, characterized in that: In step 1), the metal in the metal salt precursor is selected from one or more of Fe(II), Co(II), Cu(II) and Pb(II); The mass ratio of the metal in the metal salt precursor to the micron-sized aluminum powder is (0.1-5):100; The ultrasonic treatment time is 10~30 min; the stirring time is 8~24 h.
7. The method for preparing a metal single atom catalyst according to claim 6, characterized in that: The metal salt precursor is selected from one or more of decacarbonyl dimanganese, octacarbonyl dicobalt, dodecacarbonyl triiron, ferric acetylacetonate, cobalt acetylacetonate, copper acetylacetonate and lead acetylacetonate.
8. The method for preparing the metal single atom catalyst according to claim 5, characterized in that: In step 2), during the process of removing the solvent by rotary evaporation, the water bath temperature of the rotary evaporator is set to 50-70°C, the rotation speed is set to 120-140 rpm, and the duration is 30-120 min.
9. The method for preparing the metal single atom catalyst according to claim 5, characterized in that: In step 3), the temperature regime for the calcination treatment is: starting from room temperature, heating to 100-450°C at a heating rate of 1-5°C / min, and keeping the temperature for 1-3 h.
10. Use of the metal single atom catalyst described in any one of claims 1 to 4 in improving the thermal properties of materials.
Citation Information
Patent Citations
Micron-sized core-shell thermite and preparation method thereof
CN112341300A
Method for continuous batch synthesis of monatomic catalyst
CN113634288A
Aluminum-copper core-shell structure metal fuel with catalytic effect and preparation method thereof
CN114853554A
Vapor phase layer-by-layer etching method for spontaneous oxidation layer of aluminum powder
CN117753969A
Efficient synthesis method of high-loading-capacity monatomic catalyst
CN118437411A
